2013
DOI: 10.1080/13811118.2013.748404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Contagion on Non-Suicidal Self-Injury: A Review of the Literature

Abstract: In this review, we explore social contagion as an understudied risk factor for non-suicidal self-injury (NSSI) among adolescents and young adults, populations with a high prevalence of NSSI. We review empirical studies reporting data on prevalence and risk factors that, through social contagion, may influence the transmission of NSSI. Findings in this literature are consistent with social modeling/learning of NSSI increasing risk of initial engagement in NSSI among individuals with certain individual and/or ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 72 publications
6
135
1
9
Order By: Relevance
“…Some of these pictures showed very severe wounds, which can be disturbing to (especially younger) users of Instagram, and that those severe wounds generated more comments than pictures of mild wounds. Furthermore, as studies have shown that NSSI can be socially contagious (Jarvi et al 2013), pictures on Instagram might put adolescents at risk to initiate NSSI or might be triggering for users already engaging in NSSI (Lewis & Baker, 2011). Initiatives to remove those pictures off social media for those reasons have recently gone as far as users signing petitions to eliminate accounts with specific NSSI content (Ross, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these pictures showed very severe wounds, which can be disturbing to (especially younger) users of Instagram, and that those severe wounds generated more comments than pictures of mild wounds. Furthermore, as studies have shown that NSSI can be socially contagious (Jarvi et al 2013), pictures on Instagram might put adolescents at risk to initiate NSSI or might be triggering for users already engaging in NSSI (Lewis & Baker, 2011). Initiatives to remove those pictures off social media for those reasons have recently gone as far as users signing petitions to eliminate accounts with specific NSSI content (Ross, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent nightmares are a risk factor for suicidal thoughts and behaviors (Li et al, 2010;Pigeon, Pinquart, & Conner, 2012;Sjostrom et al, 2009), and suicidal thoughts and behaviors are also sometimes contagious, e.g., in 'copycat' suicides (Jeong et al, 2012;Yang et al, 2012). Self-injurious behaviors are similarly associated with both nightmares (Wong, Brower, & Zucker, 2011) and contagion (Jarvi, Jackson, Swenson, & Crawford, 2013). Thus, there may be an underlying tendency to imitate others among self-harming individuals, which is consistent with the possibility that there is an underlying voluntary and involuntary tendency to imitate others' behaviors among suicidal individuals.…”
Section: Mirror Behaviors Disturbed Dreaming and Psychopathologymentioning
confidence: 50%
“…See Table 4 for the fourfactor model and factor loadings. Although empirical evidence has shown peer identification/influence to be salient in adolescent NSSI (Jarvi et al, 2013;Prinstein et al, 2010;You, Lin, Fu, & Leung, 2013) and therefore needs to be taken into account when assessing functions of NSSI, these functions were not commonly reported by adolescents in the current self-report study.…”
mentioning
confidence: 50%
“…A further challenge is the aspect of social contagion that has been reported for NSSI (Jarvi, Jackson, Swenson, & Crawford, 2013), for example peer socialization effects (Deliberto & Nock, 2008;Prinstein et al, 2010), to which adolescents probably are especially susceptible. The Internet is a natural part of life for most adolescents and offers plenty of information about NSSI (Lewis et al, 2011;Lewis et al, 2012;Purington & Whitlock, 2010).…”
Section: Nssi and Adolescencementioning
confidence: 99%
See 1 more Smart Citation